Living customary water tenure in rights-based water management in Sub-Saharan Africa - van Koppen, Barbara (International Water Management Institute, 2022)
Living customary water tenure is the most accepted socio-legal system among the large majority of rural people in sub-Saharan Africa. Based on literature, this report seeks to develop a grounded understanding of the ways in which rural people meet their domestic and productive water needs on homesteads, distant fields or other sites of use, largely outside the ambits of the state. Taking the rural farming or pastoralist community as the unit of analysis, three components are distinguished. The first component deals with the fundamental perceptions of the links between humankind and naturally available water resources as a commons to be shared by all, partially linked to communities’ collective land rights. The second component deals with the sharing of these finite and contested naturally available water resources, especially during dry seasons and droughts. Customary arrangements shape both the ‘sharing in’ of water resources within communities and the ‘sharing out’ with other customary communities or powerful third parties. Since colonial times, communities have been vulnerable to those third parties grabbing water resources and overriding customary uses and governance. The third component deals with infrastructure to store and convey water resources. Since time immemorial, communities have invested in infrastructure for self supply, ranging from micro-scale soil moisture retention techniques to large-scale collective deep wells. As increasingly recognized in both the water, sanitation and hygiene (WASH) and irrigation sectors, this component of self supply is rapidly expanding. In all three components, local diversity is high, with gender, class and other social hierarchies intertwining with social safety nets, neighborliness and moral economies. The study derives two sets of implications for state and non-state policies, laws and interventions. First, state legislation about the sharing of water resources should recognize and protect living customary water tenure, especially through due process in ‘sharing out’ water with powerful third parties. Remarkably, water law, which is dominated by permit systems in sub-Saharan Africa, lags behind other legislation in recognizing customary water tenure (see IWMI Research Report 182). Second, by taking communities’ self supply for multiple uses as a starting point for further water infrastructure development, the WASH, irrigation and other sectors can follow the priorities of communities, including the most vulnerable; identify cost-effective multi-purpose infrastructure; develop local skills; and, hence, contribute more sustainably to achieving more United Nations Sustainable Development Goals (SDGs), in particular SDGs 1, 2, 3, 5, 6 and 13. Further historical and interdisciplinary research to achieve these benefits is recommended.